Aesthetic replacement of an anterior tooth using the natural tooth as a pontic; an innovative technique - Aamir Rashid Purra; Mubashir Mushtaq (Elsevier, 2013)
This article presents a novel technique for replacing an anterior tooth. A new modification to the clinical technique of direct fabrication of a resin-bonded bridge was employed, in which the patient's natural tooth was used as a pontic. Treatment with this modification led to overall improved aesthetics and reduced treatment cost. The natural tooth pontic was stabilized in the extraction socket with a resin-wire splint as a provisional restoration to maintain the gingival architecture while the permanent bridge was being constructed. Keywords: Aesthetics, Natural tooth pontic, Resin-bonded bridge